2015
DOI: 10.17261/pressacademia.2015312959
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of corporate bankruptcy: evidence from West African s SMEs

Abstract: Bankruptcy is a legal proceeding in which a corporation has become insolvent and therefore cannot pay its obligations .The purpose of this paper is to assess the default risk or to predict bankruptcy of some public firms listed on the stock Exchange Securities (BRVM) of West African Economic and Monetary Union (WAEMU) and on the Ghana Stock Exchange (GSE). 34 companies from different sectors and sizes have taken place in this study. The main purpose is to measure the performance of these companies that constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In 1988, Merrick Hutchinson used Principal Components Analysis (PCA) to recognize the monetary attributes of little firms to accomplish citation on the UK unlisted securities market (Adalessossi, 2015). In 1992, Laitinen endeavored to foster a model to failure of newly founded firms (Weinzimmer et al, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1988, Merrick Hutchinson used Principal Components Analysis (PCA) to recognize the monetary attributes of little firms to accomplish citation on the UK unlisted securities market (Adalessossi, 2015). In 1992, Laitinen endeavored to foster a model to failure of newly founded firms (Weinzimmer et al, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…His examination showed that it was conceivable, somewhat, to expect disappointment of new organizations in the principal year after establishment (Gilboa et al, 2008). He tracked down that the best-inferred indicators were the accompanying: stockholders' capital/total capital, cash flow/ net sales and cash flow/total debt (Adalessossi, 2015). The classifications include liquidity proportions, influence proportions, movement proportions, and benefit proportions (Courtis, 1978); reviewed a few investigations to recognize the factors helpful at anticipating disappointment gathered.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Principal Component Analysis (PCA), the statistical procedure that uses an orthogonal transformation to convert a set of observations of possibly correlated variables into a set of values of linearly uncorrelated variables called principal components started to be used in analysis and prediction of bankruptcy risk. Adalessossi (2015) used discriminant function named Z-scores model of Altman, financial ratio analysis, and the principal component analysis on a sample of 34 listed companies from different sectors and sizes in order to find out if the three methods used in this study converge toward similarity results. The comparison of the three methods indicates unanimously that, out of the 34 companies, only eight companies have had the best financial performances and are not likely to go on to bankruptcy.…”
Section: Literature Reviewmentioning
confidence: 99%